Stimulated Type I Collagen Turnover in Patients With Giant Cell Tumor of Bone - Nakashima, H.; Sugiura, H.; Nishida, Y.; Yamada, Y.; Tabata, I.; Ishiguro, N. (Calcified tissue international, 2003)
The aim of this study was to determine type I collagen turnover in giant cell tumor of bone (GCT) by biochemical markers of type I procollagen aminoterminal propeptide (PINP) and type I collagen carboxyterminal telopeptide (ICTP) as synthesis and degradation markers, respectively. The serum concentrations of PINP and ICTP were measured in 11 patients with GCT using radioimmunoassay, and analyzed by the correlation to the grades of GCT progression described by Campanacci. Serum of the 11 healthy subjects was available for comparison. The serum concentration of PINP was significantly higher in patients with GCT (82.4 +/- 46.2 ng/ml) than in controls (40.8 +/- 12.1 ng/ml) (P < 0.01), and that of ICTP was also significantly higher in GCT (5.3 +/- 2.0 ng/ml) than in controls (3.2 +/- 0.8 ng/ml) (P < 0.01). In GCT, the PINP concentration of grade 3 (127.6 +/- 38.8 ng/ml) was higher than that in grade 1 patients (46.9 +/- 4.8 ng/ ml) (P < 0.01). ICTP concentration of both grades 2 (7.1 +/- 1.4 ng/ml) and 3 (5.8 +/- 1.8 ng/ml) patients was significantly higher than that of grade 1 (3.5 +/- 0.6 ng/ ml) patients (P < 0.01, P < 0.05, respectively). Two cases of serum concentration of PINP and ICTP after resection of GCT demonstrated that these biomarkers decreased to the control levels in the absence of GCT. Our results indicated that type I collagen turnover evaluated by ICTP and PINP was stimulated in the presence of GCT. Moreover, this enhanced metabolic turnover reflects the grade of GCT.